MODEL PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA MATERI KEKAYAAN BUDAYA INDONESIA DI SEKOLAH DASAR - Kamilah, Tuti'atul; Syafawani, Nurul Amatullah; Suci, Ulan; Puteri, Analia Kurnia; Siswoyo, Andika Adinanda; Suliha, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the learning outcomes of third-grade students in the Civics Education (PKn) subject on the material of Indonesian Cultural Wealth through the implementation of the Project Based Learning (PjBL) model. This research uses the Classroom Action Research (CAR) method, which was carried out in two cycles at SDN Bilaporah 01 with 21 students as the research subjects. Data collection techniques were conducted through learning outcome tests and learning observation sheets. The results of the study show that the implementation of the PjBL model is able to improve students' learning outcomes. The completeness percentage of learning increased from 86% in cycle 1 to 95.24% in cycle 2, while the class average increased from 88.57 to 91.9. In addition, students became more active and enthusiastic during the learning process. Thus, the Project Based Learning (PjBL) model is effective for improving students' learning outcomes in Civics Education at elementary school.